2019
DOI: 10.1177/0004865819868004
|View full text |Cite
|
Sign up to set email alerts
|

“They just don’t care about us!”: Police custody experiences for young men with histories of injecting drug use

Abstract: Young men (aged 18–24) represent a quarter of all episodes of police custody detention for adult males in Victoria, Australia. Despite this, little is known about their experience. Using Bacchi’s Foucauldian-influenced “What’s the problem represented to be?” approach and data from interviews with 28 young men with histories of injecting drug use who were detained in police custody prior to adult prison, we aim to address this gap in the literature. We highlight how dividing practices of discrimination made pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…One young man, who was among at least seven who self-harmed in custody, including hunger striking, cutting, and punching walls (see Walker, Higgs, et al, 2019), described spending a night at the MCC in a “padded cell with a suicide blanket,” because he had been “head-butting” a brick wall. A simultaneous process for gaining the attention of staff and voicing their despair and powerlessness when requests for care or medication were delayed or ignored, and a potential mechanism for rejecting dominant truths imposed upon them as second-class citizens, self-harm made possible material effects even beyond those of the physical harms imposed upon themselves.…”
Section: Resultsmentioning
confidence: 99%
“…One young man, who was among at least seven who self-harmed in custody, including hunger striking, cutting, and punching walls (see Walker, Higgs, et al, 2019), described spending a night at the MCC in a “padded cell with a suicide blanket,” because he had been “head-butting” a brick wall. A simultaneous process for gaining the attention of staff and voicing their despair and powerlessness when requests for care or medication were delayed or ignored, and a potential mechanism for rejecting dominant truths imposed upon them as second-class citizens, self-harm made possible material effects even beyond those of the physical harms imposed upon themselves.…”
Section: Resultsmentioning
confidence: 99%
“…You've done as you're told, as I asked you to, then you can have X. ' (CO41) (see for similar Choongh 1997;Walker et al 2020). This generated in young participants the same 'extreme scepticism about the utility of rights' that Choongh (1997: 177) identified in adult detainees-as Hussain observed: 'there's no point in ringing the bell, they're just gonna waste your time' .…”
Section: Deprivation Of Autonomy-'you Feel Like You Can't Say Nothing...mentioning
confidence: 99%
“…(Megan), (see for similar Hazel et al 2003;Jones 2007), recalling the pain of prisoner 'underload' (Toch 1982). These privations tended to magnify pre-existing vulnerabilities (see for similar Walker et al 2020), and could be particularly difficult for those who were on medication:…”
Section: Deprivation Of Liberty-'stuck In a Cage'mentioning
confidence: 99%
See 1 more Smart Citation
“…Common problems faced in prison health care include vulnerability, physical and mental stress, and associated social determinants of poor health 4 . These are reflected among watch‐house detainees 5,6 . A review of 505 coroners’ reports pertaining to deaths in police custody in Australia between 1991 and 2016 revealed that 43 (9%) occurred in a police station, police vehicle, police cell, or watch‐house; 7 of these, 15 occurred in Queensland, and 17 were Aboriginal or Torres Strait Islander people.…”
mentioning
confidence: 99%